Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41467-017-01392-9
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 receptor alpha 2 cooperates with EGFRvIII signaling to promote glioblastoma multiforme

Abstract: The interleukin-13 receptor alpha2 (IL-13Rα2) is a cancer-associated receptor overexpressed in human glioblastoma multiforme (GBM). This receptor is undetectable in normal brain which makes it a highly suitable target for diagnostic and therapeutic purposes. However, the pathological role of this receptor in GBM remains to be established. Here we report that IL-13Rα2 alone induces invasiveness of human GBM cells without affecting their proliferation. In contrast, in the presence of the mutant EGFR (EGFRvIII), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 52 publications
2
61
0
1
Order By: Relevance
“…Our results showed that IL13RA2 could contribute to cell apoptosis and inhibiting cell proliferation and migration without addition of IL‐13. This phenomenon has also appeared in other reports . One illustration is that serum may contain sufficient IL‐13 or other ligands.…”
Section: Discussionsupporting
confidence: 70%
“…Our results showed that IL13RA2 could contribute to cell apoptosis and inhibiting cell proliferation and migration without addition of IL‐13. This phenomenon has also appeared in other reports . One illustration is that serum may contain sufficient IL‐13 or other ligands.…”
Section: Discussionsupporting
confidence: 70%
“…One of the most interesting analyses is focused on the nuclear role of EGFR vIII , as this function is suggested to be very relevant [144,145]. erefore, EGFR vIII interaction with oncostatin M receptor (OSMR) can be considered interesting, as it may be possible to design molecules inhibiting such interaction for therapeutic purposes [146]. In general, results of research conducted so far indicate that the majority of EGFR vIII activity is exhibited outside the nucleus, while its low kinase activity may be compensated by uniquely high stability [17,121,[123][124][125][147][148][149].…”
Section: Egfr VIII Mechanism Of Actionmentioning
confidence: 99%
“…However, there were other advantages for targeting IL‐13Rα2 with the IL‐13Rα2–lytic hybrid peptide in GB cells as this peptide could affect both the phosphorylation of Akt and Erk1/2 and the activation of AP‐1 by IL‐13 in GB cells, which are known as significant components of IL‐13Rα2 signaling by IL‐13 for cancer invasion and metastasis, in which IL‐13 enhances Erk1/2 and AP‐1 (Fujisawa et al., ). Further study using this peptide is needed to elucidate the underlying mechanism as well as the role of IL‐13Rα2, as the details of the signaling mechanism downstream of IL‐13Rα2 remain unclear and the receptor interacts with other receptor such as EGFRvIII in GB cells, as recently reported (Newman et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…The monomeric receptor interleukin-13 receptor alpha 2 (IL-13Rα2), which has a higher affinity to interleukin-13 (IL-13) than that of IL-13Rα1 (Andrews, Holloway, Puddicombe, Holgate, & Davies, 2002), has significant roles in GB cells and can be used as a decoy receptor (Newman et al, 2017;Rahaman et al, 2002). Thus, several groups have reported the potency of targeting IL-13Rα2 for GB therapy (Brown et al, 2016;Joshi, Husain, & Puri, 2000;Sattiraju et al, 2017;Sengupta, Thaci, Crawford, & Sampath, 2014;Thaci et al, 2014).…”
Section: Introductionmentioning
confidence: 99%